Pathophysiological Consequences of Neuronal α-Synuclein Overexpression: Impacts on Ion Homeostasis, Stress Signaling, Mitochondrial Integrity, and Electrical Activity - Tolö, Johan; Taschenberger, Grit; Leite, Kristian; Stahlberg, Markus A.; Spehlbrink, Gesche; Kues, Janina; Munari, Francesca; Capaldi, Stefano; Becker, Stefan; Zweckstetter, Markus; Dean, Camin; Bähr, Mathias; et al. (Frontiers in Molecular Neuroscience, 2018)
α-Synuclein (α-Syn) is intimately linked to the aetiology of Parkinson´s Disease, as mutations and even subtle increases in gene dosage result in early onset of the disease. However, how this protein causes neuronal dysfunction and neurodegeneration is incompletely understood. We thus examined a comprehensive range of physiological parameters in cultured rat primary neurons overexpressing α-Syn at levels causing a slowly progressive neurodegeneration. In contradiction to earlier reports from non-neuronal assay systems we demonstrate that α-Syn does not interfere with essential ion handling capacities, mitochondrial capability of ATP production or basic electro-physiological properties like resting membrane potential or the general ability to generate action potentials. α-Syn also does not activate canonical stress kinase signalling converging on SAPK/Jun, p38 MAPK or Erk kinases. Causative for α-Syn-induced neurodegeneration are mitochondrial thiol oxidation and activation of caspases downstream of mitochondrial outer membrane permeabilization, leading to apoptosis-like cell death execution with some unusual aspects. We also aimed to elucidate neuroprotective strategies counteracting the pathophysiological processes caused by α-Syn. Neurotrophic factors, calpain inhibition and increased lysosomal protease capacity showed no protective effects against α-Syn overexpression. In contrast, the major watchdog of outer mitochondrial membrane integrity, Bcl-Xl, was capable of almost completely preventing neuron death, but did not prevent mitochondrial thiol oxidation. Importantly, independent from the quite mono-causal induction of neurotoxicity, α-Syn causes diminished excitability of neurons by external stimuli and robust impairments in endogenous neuronal network activity by decreasing the frequency of action potentials generated without external stimulation. This latter finding suggests that α-Syn can induce neuronal dysfunction independent from its induction of neurotoxicity and might serve as an explanation for functional deficits that precede neuronal cell loss in synucleopathies like Parkinson´s disease or dementia with Lewy bodies.